Board characteristics and board committees in the Greek corporate governance - Chris Grose; Dimitrios Koufopoulos; Ioannis Gkliatis; Konstantinos Athanasiadis; Michail Fygkioris (CES Working Papers, 2021)
The paper investigates board characteristics and committees' structure in the Athens Stock Exchange (ATHEX) using unique data culled from the database of the Hellenic Observatory of Corporate Governance. The current corporate governance framework applying in Greece is also analysed while comparisons with the international experience are offered. In Greece, while the Law calls for the need to have a Committee comprising of non-executive Board of Directors (BoD) members, it permits the participation of non-BoD members that collectively fulfill the independence criteria as laid out by Law 4706. L.4449 introduced the current Audit Committee composition and operation framework and the accompanying tighter monitoring role on the part of the Hellenic Capital Market Commission (HCMC) and the Hellenic Accounting and Auditing Oversight Board (HAASOB), has undoubtedly overhauled all the audit framework. The average number of committees per listed firm in the Greek stock exchange almost reached the two-committee threshold only in 2018. Average board size is 7.85 members slightly smaller than the average size for major markets around the globe. This shows the potential for an increase in Board size given also recent regulatory changes necessitating the gender representation of at least 25% in the Board of public firms.
Keywords: 330; board size; audit committee; corporate governance; Greek corporate governance code